Financialisation, Welfare Retrenchment and Subsistence Debt in Britain. Issue 2 (23rd February 2020) - Dagdeviren, Hulya; Balasuriya, Jiayi; Luz, Sheila; Malik, Ali; Shah, Haider
ABSTRACT: This paper investigates the dynamics of low income household (LIH) indebtedness under austerity in Britain. Building on a range of political economy studies on the role of the state in the process of financialisation, the paper discusses the transition in the nature of LIH indebtedness in connection to the recent welfare retrenchment. The analysis of survey data and semi-structured interviews establishes the fact that LIHs experienced the greatest growth in unsecured debt to income ratio under austerity. More importantly, unlike the pre-crisis period when LIHs' debt reflected a desire 'to keep-up with the Joneses', post crisis, a different form of indebtedness has emerged. There has been a notable rise in debt for essential needs such as rent, food and utility services. Liabilities are not only owed to banks and fringe providers (payday lenders, money shops, etc.) but also to non-financial companies and local authorities which have become de facto creditors. The evidence in this paper shows that these changes are directly related to the austerity measures, especially, to the cuts in welfare budgets and the intensified use of 'disciplinary techniques' in the form of sanctions and administrative / legal enforcement of debt collection by public sector entities.